2021
DOI: 10.1186/s12866-021-02358-0
|View full text |Cite
|
Sign up to set email alerts
|

Complete genomic sequence and phylogenomics analysis of Agrobacterium strain AB2/73: a new Rhizobium species with a unique mega-Ti plasmid

Abstract: Background The Agrobacterium strain AB2/73 has a unique host range for the induction of crown gall tumors, and contains an exceptionally large, over 500 kbp mega Ti plasmid. We used whole genome sequencing to fully characterize and comparatively analyze the complex genome of strain AB2/73, including its Ti plasmid and virulence factors. Results We obtained a high-quality, full genomic sequence of AB2/73 by a combination of short-read Illumina seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 101 publications
(99 reference statements)
1
12
0
Order By: Relevance
“…AB2/73 which was isolated from Lippia canescens in the USA (Anderson & Moore, 1979). Recently, Hooykaas and Hooykaas (2021) suggested that this strain belongs to a novel Rhizobium species, which is closely related to Rhizobium dioscoreae according to our results. The second putative species includes Ti plasmid‐carrying strains 17‐2069‐2b and 17‐2069‐2c isolated from blackberry (Weisberg et al, 2022).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…AB2/73 which was isolated from Lippia canescens in the USA (Anderson & Moore, 1979). Recently, Hooykaas and Hooykaas (2021) suggested that this strain belongs to a novel Rhizobium species, which is closely related to Rhizobium dioscoreae according to our results. The second putative species includes Ti plasmid‐carrying strains 17‐2069‐2b and 17‐2069‐2c isolated from blackberry (Weisberg et al, 2022).…”
Section: Discussionsupporting
confidence: 75%
“…For all analyses reported in this study, annotations produced by Prokka (Galaxy Version 1.13) (Seemann, 2014) were used. Annotation of particular sequences of interest and metabolic pathway prediction were performed using eggNOG-mapper (version emapper-2.1.9) (Cantalapiedra et al, 2021) based on eggNOG orthology data (Huerta-Cepas et al, 2018), as well as with BlastKOALA (last accessed on November 2022) (Kanehisa et al, 2016). For eggNOGmapper, sequence searches were performed using DIAMOND version 2.0.11 (Buchfink et al, 2021).…”
Section: Genome Assembly Error-correction and Annotationmentioning
confidence: 99%
See 1 more Smart Citation
“…R. rhizogenes changes plant organ morphology (Veena & Taylor, 2007 ; Bourras et al , 2015 ), known as hairy root disease, by integrating a part of a root‐inducing plasmid containing so‐called root oncogenic loci genes into the host cell genome. The expression of root oncogenic loci genes leads to the formation of new roots as a disease phenotype (Veena & Taylor, 2007 ; Hooykaas & Hooykaas, 2021 ), which involves induced expression of KNOTTED1‐LIKE HOMEOBOX ( KNOX ) TFs and cell cycle regulator genes in the host plant (Stieger et al , 2004 ). KNOX TFs are known to participate in meristem maintenance and organ patterning (Hake et al , 2004 ).…”
Section: Microbes Alter Fundamental Root Development Processes For Ac...mentioning
confidence: 99%
“…The IAM pathway of IAA synthesis is the best-characterized pathway in bacteria which mainly exists in Pseudomonas savastanoi and A. tumefaciens [ 41 – 43 ]. The main genes driving the IAM pathway are iaam and iaah , which encode tryptophan monooxygenase and indole-3-acetamide hydrolase, respectively [ 44 , 45 ]. Tryptophan monooxygenase catalyzes the conversion of L-tryptophan to indole-3-acetamide (IAM), and indole-3-acetamide hydrolase further catalyzes the hydrolysis of IAM to IAA [ 46 ].…”
Section: Introductionmentioning
confidence: 99%